Fates of petroleum during the deepwater horizon oil spill: A chemistry perspective - Overton, Edward B.; Adhikari, Puspa L.; Radović, Jagoš R.; Passow, Uta (Frontiers in Marine Science, 2022)
We describe the initial bulk and compound specific composition of the liquid oil spilled during the Deepwater Horizon (DwH) disaster. The emphasis is on the target hydrocarbon compounds typically found in highest concentrations and on those of concern from a toxicological perspective (i.e., the target normal alkanes and isoprenoids, and PAHs on U.S. Environmental Protection Agency’s (EPA) priority list with their alkyl homolog compounds), and/or those relevant for forensic fingerprinting of spill residues (i.e., sulfur containing PAHs and biomarker compounds). Weathering changed the oil’s composition in various environmental compartments. These compositional changes and potential environmental impacts of the remaining weathered residues are presented in this paper. Biodegradation occurred in both surface and subsurface environments while photooxidation primarily modified and removed hydrocarbons in floating oil slicks. The volatile, soluble and highly labile C1 to C10 hydrocarbons were rapidly degraded in the water column and/or emitted to the atmosphere (evaporation). The semi-volatile hydrocarbons (labile C10 to C25) that remained in the water column and floating oil on the water’s surface were lost from oil residues during weathering. The heavy nonvolatile and insoluble hydrocarbons (recalcitrant C25+) were least affected by initial weathering processes in 2010. The composition of the residual oil fraction in surface floating oil was further altered by the addition of oil soluble oxy hydrocarbons produced from photooxidation. During 2011 and 2012 the resulting highly insoluble recalcitrant C25+ oily residues remained on the shorelines, bottom sediments, or bound to suspended particulates in the water column, with detectable residues mostly returning to near pre-spill levels by 2015 to 2020. Some recalcitrant oil residues can still be found at various locations, including some coastal environments (e.g., marshes), or deep-water sediments, at very low levels, ten years after the spill.